2020
DOI: 10.1002/dev.22018
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the dynamic nature of vagal responsivity in infancy: Methodological innovations and theoretical implications

Abstract: According to polyvagal theory, rapid modulation of the vagal brake develops early in infancy and supports social interactions. Despite being viewed as a dynamic system, researchers typically assess vagal regulation using global measures of respiratory sinus arrhythmia (RSA; an index of vagal tone). This study sought to capture the dynamic property of RSA and evaluate individual differences in within-infant RSA responsivity during mother-infant interaction. RSA was evaluated in a sample of 135 6-month-old Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Rather than focusing on trajectories of change in RSA across varying social contexts (e.g., change from play to stressful interactions, i.e., reactivity, or return to play, i.e., recovery), examining within‐person variability in RSA during a task offers insight into dynamic changes in RSA that are thought to facilitate real‐time socioemotional responding during a specific interactive context. Consistent with polyvagal theory (e.g., Porges, 2007) and the assertion that greater temporal variability around one’s own mean level of RSA in the absence of psychosocial challenge suggests difficulties maintaining homeostasis in vagal functioning, prior work from our group demonstrated that more second‐by‐second variability (within‐infant SD ) in infant RSA during free play predicted elevated behavior problems in toddlerhood (Somers et al., 2020). Similarly, Berry et al.…”
Section: Introductionsupporting
confidence: 81%
“…Rather than focusing on trajectories of change in RSA across varying social contexts (e.g., change from play to stressful interactions, i.e., reactivity, or return to play, i.e., recovery), examining within‐person variability in RSA during a task offers insight into dynamic changes in RSA that are thought to facilitate real‐time socioemotional responding during a specific interactive context. Consistent with polyvagal theory (e.g., Porges, 2007) and the assertion that greater temporal variability around one’s own mean level of RSA in the absence of psychosocial challenge suggests difficulties maintaining homeostasis in vagal functioning, prior work from our group demonstrated that more second‐by‐second variability (within‐infant SD ) in infant RSA during free play predicted elevated behavior problems in toddlerhood (Somers et al., 2020). Similarly, Berry et al.…”
Section: Introductionsupporting
confidence: 81%
“…By contrast, lower baseline infant RSA and smaller decreases in infant RSA (i.e., change in average RSA from baseline to a stressor task) in response to stress have been associated with deficits in self-regulation, and social, emotional, and behavioral problems in childhood (Feldman, 2009; Field & Diego, 2008; Porges, 2001; Porges et al, 1996). Prior work from our group demonstrated that higher within-infant variability (standard deviation, SD ) of RSA during free play, suggestive of difficulties maintaining homeostasis in vagal functioning in the absence of environmental challenges, predicted elevated behavior problems in toddlerhood (Somers, Curci, & Luecken, 2020). Context-appropriate infant RSA (indicated by higher within-infant mean and lower within-infant SD of RSA during free play) may enable infants to more effectively participate in social interactions, leading to smoother Parent × Child interactions and more sensitive caregiving (e.g., Perry, Mackler, Calkins, & Keane, 2014).…”
Section: Infant Vagal Functioning and Emotion Regulationmentioning
confidence: 72%
“…describe another novel approach: stressing caregivers during caregiver-child face-toface interactions. They find that while caregiver behavior was not rated differently between stress and non-stressed caregivers, infant cortisol responses and infant distress reflected the stress condition, and caregivers rated themselves more negatively following the stress exposure Somers et al (2022). present data suggesting more nuanced measurement of respiratory sinus arythmia (RSA, specifically, intraindividual variability in RSA during a task at 6 months) offers predictive value.…”
mentioning
confidence: 51%
“…Somers et al. (2022) present data suggesting more nuanced measurement of respiratory sinus arythmia (RSA, specifically, intraindividual variability in RSA during a task at 6 months) offers predictive value. In their article, Mexican‐American infants with greater RSA variability at 6 months were reported by parents to have more behavior problems at 18 months.…”
Section: Infancymentioning
confidence: 99%